Knowledge about ultraviolet radiation (UVR) and attitudes and behaviour regarding gel manicure according to the age of women - Malinowska-Borowska, Jolanta; Buczkowska, Marta (Journal of Education, Health and Sport, 2023)
Introduction and purpose. Nowadays, artificial gel nails, which require Ultraviolet Radiation (UVR) for polymerization, steadily gain popularity. Gel manicure dried with UV lamps has become a regular part of many women's beauty routines. However, its safety remains controversial. The aim of the study was to assess the women’s knowledge of UVR and their attitudes towards UV nail exposure and its impact on human health. Material and methods. The study was carried out from January to March 2020 with the use of PAPI and CAWI method. The study population consisted of 188 women living in the Silesian Voivodeship in Poland. The mean age was 31.7 ±12.4. The majority of women were familiar with UV nail polish drying devices (74%). Most of the respondents were regularly using UV lamps (51.1%). Results. 62% of women aged 18-25 regularly got UV manicure, whereas only 29% of women older than 40 years (p<0.001). Most of the respondents got UV manicure at beauty salon. However, 37% of women got it also at home. Self-manicure was mostly popular among women at age 18-25 (p<0.001). Only 18.7% put sunscreen on hands and 10.8 % wore fingerless gloves. Simultaneous antibiotic therapy or artificial sunbathing was not a contraindication for 15% and 8% of women, respectively. The knowledge of respondents about UV radiation was poor. The rate of correct responses was 54.7%. Conclusions. While existing research suggests a low risk of carcinogenesis resulting from UV nail lamp use, ways to minimize any risk should be kept in mind. Dermatologists should educate patients, especially those with photosensitivity disorders, tanning bed history or with family history of skin cancer and raise their awareness about the potential health risk of UV manicure. Photoprotection and fingerless gloves should be accessible in beauty salons and recommended to use during UV manicure. Safety regulations concerning UV lamps are needed because they are very often self-operated by many women at home.